Comment on "Rivalry in Bacillus subtilis colonies: enemy or family?". Issue 13 (24th March 2020) - Matoz-Fernandez, Daniel; Arnaouteli, Sofia; Porter, Michael; MacPhee, Cait E.; Stanley-Wall, Nicola R.; Davidson, Fordyce A.
Abstract : It is well known that biofilms are one of the most widespread forms of life on Earth, capable of colonising almost any environment from humans to metals.